Heart of a samurai : based on the true story of Nakahama Manjiro - Preus, Margi (Amulet Books, 2010)
In 1841, rescued by an American whaler after a terrible shipwreck leaves him and his four companions castaways on a remote island, fourteen-year-old Manjiro, who dreams of becoming a samurai, learns new laws and customs as he becomes the first Japanese person to set foot in the United States.